The Complexity of Arabic Scrabble : Problems and Analysis of Using Arabic Alphabet in Scrabble - Fauzan Hakami; Muaz Kalimatun Nabil; Doni Wahidul Akbar; Miatin Rachmawati; Ammar Madi (PPPBA, 2024)
English scrabble is a prestigious language board game in the world. In addition to being a medium of vocabulary mastery, English scrabble is also an international tournament. Ironically, this is not shared by Arabic scrabble even though it is one of the languages that most speakers and learners learn. The uniqueness of Arabic and the difference in structure with English are the main factors causing the stagnant Arabic scrabble game. Finding the complexity of problems in terms of language structure and Arabic scrabble components is the purpose of this study. By coming up with a theory that will make Arabic scrabble more adaptively accepted by even non-native speakers. Descriptive qualitative methods were used in this study with data sourced from observations, interviews, and literature studies. The subjects observed and interviewed were students of UHAMKA Arabic Language Education. Other sources refer to related books and journals. The data were analyzed using comparative and reduction techniques. Overall, the inequality of tile distribution of the Arabic alphabet and the English alphabet, then diacritical symbols (harakat) as Arabic vowels, and the need for editions that are friendly to foreign speakers are the three points of the final results of this study.